THE BEHAVIOR OF 210PB OFF COAST ULSAN, GAMPO AND POHANG WATERS, KOREA - M. Muslim (JOURNAL OF COASTAL DEVELOPMENT, 2009)
During summer of August 2000, the behavior of 210Pb was studied in off coast Ulsan, Gampo and Pohangwaters, Korea as an area potentially upwelling occur. Water samples were collected vertically inshore andoffshore at each station. The highest of 210Pb activity occurred in the surface layer as derivate fromatmosphere and then decreased with increasing depth. The lower 210Pb activity in bottom layer was causedby scavenging of particulate matter and strong affinity of unsupported 210Pb to soil and sediment particles.In middle layer of the water column activity of 210Pb fluctuated due to water masses of North Korea ColdWater (NKCW) that flows in this layer. The water mass of NKCW also affect on increasing dissolved oxygen(DO), where the highest of DO concentration occurred in this middle layer. The vertical distribution of 210Pbin the study area was generally not different between inshore and offshore, and the activity of 210Pb thatdetermine also was not significant different with previous studies.